Zooming Into the Microbiota of Home-Made and Industrial Kefir Produced in Greece Using Classical Microbiological and Amplicon-Based Metagenomics Analyses - Kazou, Maria; Grafakou, Andriana; Tsakalidou, Effie; Georgalaki, Marina (Frontiers in Microbiology, 2021)
Kefir is a high nutritional fermented dairy beverage associated with a wide range of health benefits. It constitutes a unique symbiotic association, comprising mainly lactic acid bacteria, yeasts and occasionally acetic acid bacteria, which is strongly influenced by the geographical origin of the grains, the type of milk used and the manufacture technology applied. Until recently, kefir microbiota has been almost exclusively studied by culture-dependent techniques. However, high-throughput sequencing, alongside omics approaches, has revolutionized the study of food microbial communities. In the present study, the bacterial and yeast/fungal microbiota of four home-made samples (both grains and drinks), deriving from well spread geographical regions of Greece, and four industrial beverages, was elucidated by culture-dependent and -independent analyses. In all samples, classical microbiological analysis revealed varying populations of LAB and yeasts, ranging from 5.32 to 9.60 log CFU mL-1 or g-1, and 2.49 to 7.80 log CFU mL-1 or g-1, respectively, while in two industrial samples no yeasts were detected. Listeria monocytogenes, Salmonella spp. and Staphylococcus spp. were absent from all the samples analyzed, whereas Enterobacteriaceae were detected in one of them. From a total of 123 isolates, including 91 bacteria and 32 yeasts, Lentilactobacillus kefiri, Leuconostoc mesenteroides and Lactococcus lactis as well as Kluvyeromyces marxianus and Saccharomyces cerevisiae were the mostly identified bacterial and yeast species, respectively, in the home-made samples. On the contrary, Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus and Lacticaseibacillus rhamnosus along with Debaryomyces hansenii and K. marxianus were the main bacterial and yeast species, respectively, isolated from the industrial beverages. In agreement with the identification results obtained from the culture-dependent approaches, amplicon-based metagenomics analysis revealed that the most abundant bacterial genera in almost all home-made samples (both grains and drinks) were Lactobacillus and Lactococcus, while Saccharomyces, Kazachstania and Kluvyeromyces were the predominant yeasts/fungi. On the other hand, Streptococcus, Lactobacillus and Lactococcus as well as Kluvyeromyces and Debaryomyces dominated the bacterial and yeast/fungal microbiota, respectively, in the industrial beverages. This is the first report on the microbiota of kefir produced in Greece by a holistic approach combining classical microbiological, molecular and amplicon-based metagenomics analyses.